DOUBLE BOND ISOMERIZATION OF PHENYLPROPENOIDS CATALYZED BY IN SITU GENERATED NICKEL(0) PHOSPHINE - Gustini, Nunik
Phenylpropenoids are a well-known set of naturally occurring compounds obtained from plants such as basil, nutmeg, pimento, laurel, lemongrass, and fennel. Phenylpropenoids are classified into 2-propenylbenzene and 1-propenylbenzene. Double bond isomerizations of 2-propenylbenzene are important transformations because the corresponding trans-isomers are high-value fine chemicals for pharmaceuticals, fragrance, or food industries. Double bond isomerizations have been reported to occur by bases, heterogeneous catalysts, or homogeneous catalysts. Conventional double bond isomerizations were commonly catalyzed by bases such as KOH and NaOH in a stoichiometric amount and at very high temperature to generate low yield and low selectivity products to trans-isomers. Conventional reactions have disadvantages such as the use of strong base in large amount, long reaction time, low conversion of reactant, low selectivity of trans-isomerized products, high reaction temperature, and disposal problems of hazardous post reaction effluents. Heterogeneous catalysts employed in phenylpropenoid isomerizations include MgAl-4HT, Pt/?-Al2O3, zeolite HY, KF/Al2O3, MgAl-LDH and NiAl-LDH. The reaction condition required high temperature, yet it still gave low yield and low selectivity to trans-products. Beside heterogeneous catalysts, some homogeneous catalysts, based on late transition metals, have been reported for such isomerizations, e.g, Ru(CO)3(PR3)2, RhCl3, PdCl2(PPh3)2, PtCl2, RuCl2(PPh3)2, [RuCl2(?6-C6H5OCH2CH2OH)(L)]. Other transition metals with large abundance, for instance nickel, have also been reported for double bond isomerizations with active catalyst of Ni(0) to facilitate oxidative addition. Herein double bond isomerizations of phenylpropenoids (methyl eugenol, estragole, and 2-allylphenol) were successfully catalyzed by in situ generated Ni(0) phosphine. NiCl2(PPh3)2 precatalyst complex was prepared from NiCl2·6H2O and PPh3 in ethanol at 65 ºC in 30 minutes. Active catalyst of Ni(0) phosphine was obtained by reducing the Ni(II) complex with Zn powder in a one-pot isomerization reaction. Methyl eugenol conversion of 99%, with selectivity to trans-methyl isoeugenol of 96% and turn over frequency (TOF) of 190.1 h-1 could be achieved using 1 mol% of NiCl2(PPh3)2 in 30 min at 50 ºC. Isomerization reactions of methyl eugenol proceeded even in the absence of PPh3. Addition of excess PPh3 to the isomerizationiv reaction obtained the same result (99% conversion with selectivity to trans-methyl isoeugenol of 96%). Estragole conversion of 96%, with selectivity to trans-anethole of 95% and TOF of 15.2 h-1 could be achieved using 1 mol% of NiCl2(PPh3)2 relative to estragole in 6 h at 80 ºC. While conversion of 2-allylphenol was 95%, with selectivity to trans-2-(1-propenyl)phenol of >99% and TOF of 15.8 h-1 could be achieved using 1 mol% of NiCl2(PPh3)2 relative to 2-allylphenol in 6 h at 80 ºC. Isomerization reactions were run by using 1 mol% of NiCl2(PPh3)2 relative to reactants (methyl eugenol, estragole, or 2-allylphenol) in nitrogen atmosphere (1 atm) and acetonitrile solvent. Acetonitrile was observed to likely act not only as a solvent, but also as an important ligand for the reaction to occur. Kinetic studies showed that the isomerization of methyl eugenol was first order to methyl eugenol. The role of nitile in improving catalyst activity is still under investigations.